Student Participation in Small-Sided Games during Elementary Physical Education: A Qualitative Descriptive Study - Sejahtra Sejahtra (Sean Institute, 2026)
Unequal participation remains a practical problem in elementary physical education because conventional team games often allow confident students to dominate play while less-confident students remain peripheral. This study aimed to describe how student participation developed during small-sided games and to identify the task, peer, and teacher conditions that supported or constrained involvement. A qualitative descriptive design was implemented at SD Budi Murni 2 with 24 Grade V students and one physical education teacher. Data were obtained from four learning sessions, comprising 96 student-session observation records, chronological field notes, semi-structured interviews with eight students and the teacher, and learning documentation. Credibility was strengthened through source, technique, and time triangulation, member checking, and peer examination. The findings showed that students demonstrating consistent or highly sustained participation increased from 62.5% in the first session to 91.7% in the fourth session, while mean ball contacts rose from 9.33 to 13.67. Participation broadened most when three-versus-three formats were combined with explicit roles, compulsory team involvement, multiple targets, short rotations, and supportive peer communication. Nevertheless, smaller teams did not automatically eliminate dominance or fear of mistakes. The study concludes that small-sided games function as an inclusive pedagogical environment only when teachers deliberately regulate roles, rules, peer interaction, and emotional safety.